Liberal roots of far right activism : the anti-Islamic movement in the 21st century - Berntzen, Lars Erik (Extremism and democracy, 2020)
Far right and liberal? -- Perspectives on the far right -- Mapping a movement -- Expansion and legacy -- Worldviews -- Networks -- Mobilization -- Transnational and semi-liberal -- The toll of intolerance.